1998
DOI: 10.4141/s97-051
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of clopyralid, dicamba and MCPA by two soils with conventional and no-till management

Abstract: Shang, C. and Arshad, M. A. 1998. Sorption of clopyralid, dicamba and MCPA by two soils with conventional and no-till management. Can. J. Soil Sci. 78: 181-186. Sorption is one of the key processes controlling the fate of agrochemicals in soil systems. The sorption of agrochemicals on a soil matrix can be affected by changes in chemical and physical properties caused by different tillage practices. Clopyralid (3,6-dichloro-2-pyridinecarboxylic acid), dicamba (3,6-dichloro-2-methoxybenzoic acid), and MCPA ((4-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…It may be difficult to compare results if K F values are derived from different units of C s and C w or if C w ≤1 or if 1/ n values differ (Chen et al, 1999). However, the results are roughly within the range of previously reported values (Grey et al, 1996; Gaston et al, 1996; Matallo et al, 1998; Riise and Salbu, 1992; Ghorayshi and Bergström, 1991; Helweg, 1987; Susarla et al, 1992; Riise et al, 1994, Shang and Arshad, 1997; Socías‐Viciana et al, 1999; Liu and Weber, 1986). Higher K F values for all pesticides were found in soil from Froland with a high organic content and a low pH, which is consistent with previously mentioned literature that also reports higher increasing K F in soil with increasing organic content.…”
Section: Resultssupporting
confidence: 91%
“…It may be difficult to compare results if K F values are derived from different units of C s and C w or if C w ≤1 or if 1/ n values differ (Chen et al, 1999). However, the results are roughly within the range of previously reported values (Grey et al, 1996; Gaston et al, 1996; Matallo et al, 1998; Riise and Salbu, 1992; Ghorayshi and Bergström, 1991; Helweg, 1987; Susarla et al, 1992; Riise et al, 1994, Shang and Arshad, 1997; Socías‐Viciana et al, 1999; Liu and Weber, 1986). Higher K F values for all pesticides were found in soil from Froland with a high organic content and a low pH, which is consistent with previously mentioned literature that also reports higher increasing K F in soil with increasing organic content.…”
Section: Resultssupporting
confidence: 91%
“…The estimated k oc values varied between 35 and 147 cm 3 g −1 , with an average of 89 cm 3 g −1 , which is within the range of values reported for MCPA in the literature (Helweg, 1987; Riise et al, 1994; Shang and Arshad, 1998; Socías‐Viciana et al, 1999). Encouragingly, the degradation rate coefficient seemed to be well identified by the procedure, with the smallest coefficient of uncertainty of all estimated parameters (mean of 6.6%).…”
Section: Resultssupporting
confidence: 84%
“…As expected, the organic‐rich hollow column had a sorption coefficient approximately 12 and 2 times larger than the hilltop and slope columns, respectively (Table 7). Adsorption of the weak acid MCPA is affected by soil pH (Riise et al, 1994; Shang and Arshad, 1998). However, since the variation in soil pH was small (Table 1) and pH was much higher than the compound pK a (3.07; Nicholls, 1994), this effect was ignored and effective k oc values were estimated from the calibrated sorption coefficient k d and the organic carbon content f oc in the columns, following the relation: koc=100knormaldfoc…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that under shaded conditions, a portion of the herbicide was closely associated with the soil organic matter and soil water contents were sub-optimal for microbial activity. [25] Another process that may partly explain the above results could be the sorption of clopyralid to clay minerals of the soil matrix [26] being more important at low water contents. Rahman et al [8] found a significant correlation (r = À 0.56) between clopyralid persistence and clay content.…”
Section: Dissipation Of Clopyralid 691mentioning
confidence: 95%